Factors Affecting the Implementation and Barriers to Evidence-Based Practice among Nurse Practitioners in Hail Region, Saudi Arabia - Alshammari, Majed Shafi; Alshurtan, Raad; Alsuliman, Gadah; Alshammari, Marzoogha; Alhamazani, Housam; Alshammry, Samiha; Dayrit, Richard Dennis; Alkwiese, Mohannad (Nurse Media Journal of Nursing, 2021)
Background: While previous studies explored the implementation and barriers to evidence-based practice (EBP), there is a dearth of literature on the causative factors such as demographics that affect the implementation and barriers to EBP.Purpose: This study aimed to investigate the factors affecting the implementation of EBP and determine its barriers as perceived by nurse practitioners.Methods: This study employed a quantitative correlational design. A total of 228 staff nurses from the hospitals in the Hail region, Saudi Arabia, participated in this study through purposive sampling. The evidence-based practice questionnaire (EBPQ) and the barriers scale questionnaire were used to collect the data between June and July 2020. The descriptive statistics, t-test, and analysis of variance (ANOVA) were used to analyze the collected data.Results: The nurses showed a positive attitude (x=15.25Â±5.07), good knowledge (x=63.44Â±19.81), as well as good application of EBP (x=28.02Â±6.68) with an outstanding EBP score of 106.73 out of 168. Nursesâ€™ civil status (p<0.02), nationality (p<0.05), highest degree (p<0.01), job title (p<0.001), and years of experience (p<0.001) significantly affected the implementation of EBP. Also, the biggest barriers to EBP were: â€œNo time to read researchâ€ (94.3%), â€œResearch is not readily availableâ€ (97.8%), â€œNot capable to evaluate the quality of researchâ€ (90.4 %), and â€œUncertain whether to believe resultsâ€ (68.4%).Conclusion: Nurses have a positive attitude, good knowledge, and good application of EBP. Civil status, nationality, highest degree, job title, and years of experience were causative factors to EBP. Nurses in hospitals should undergo training continuously to be able to use EBP effectively.